29.2k views
2 votes
How do I solve for the fourth term in this sequence?

How do I solve for the fourth term in this sequence?-example-1
User Richsoni
by
5.3k points

1 Answer

3 votes

Answer:

d(4) = 64

Explanation:

d(1) = 13

d(n) = d(n - 1) + 17

where

n is the nth term

To find the 4th term we must first find the second term use it to find the 3rd term and use the 3rd term to find the 4th term

So we have

For the 2nd term

That's d(2)

We have

d(2) = d(2-1) + 17

d(2) = d(1) + 17

But d(1) = 13

d(2) = 13 + 17 = 30

For the 3rd term d(3)

That's

d(3) = d(3 - 1) + 17

d(3) = d(2) + 17

d(3) = 30 + 17 = 47

For the 4th term that's d(4)

We have

d(4) = d(4 - 1) + 17

d(4) = d(3) + 17

d(4) = 47 + 17

We have the final answer as

d(4) = 64

Hope this helps you

User Pronoob
by
6.5k points